Cognitive Engagement and Creative Thinking: Intervention with Research-Based e-Learning and Students' Social Attitudes in Learning Physics at Public High School - Santyasa, I Wayan; Suswandi, Iwan; Santyadiputra, Gede Saindra; Juniantari, Made (Indonesian Review of Physics, 2022)
Physics learning in high school is closely related to students' social attitudes in conducting cognitive engagement to achieve creative thinking. This study aims to analyze students' cognitive engagement and creative thinking using research-based e-learning (RBeL) and directed learning (DeL) about students' social attitudes. The samples were randomly selected from 4 classes (two experimental and two control classes). This study used a post-test-only control group design. Data on social attitudes and cognitive engagement were collected using questionnaires, and data on creative thinking using essay tests. Data were analyzed using a two-way Manova and hypothesis testing using a significance level of 5%. The results showed significant differences in the cognitive engagement of students who were intervened using RBeL and DeL. Intervention using RBeL was more effective than DeL in achieving cognitive engagement. There is a significant difference between the creative thinking of students who are intervened using RBeL and DeL. The RBeL intervention was more effective than DeL in achieving creative thinking. There are similarities in cognitive engagement and creative thinking among students with HSA and LSA. There was no interaction between learning models and social attitudes regarding cognitive engagement and creative thinking in students. The achievement of cognitive involvement and creative thinking of 10th-grade students in learning physics is more effective using research-based e-learning models.